Hyaluronate modified upconversion nanoparticles for near infrared light-triggered on–off tattoo systems. Issue 24 (7th March 2017) - Han, Seulgi; Beack, Songeun; Jeong, Sanghwa; Hwang, Byung Woo; Shin, Myeong Hwan; Kim, Hyemin; Kim, Sungjee; Hahn, Sei Kwang
Abstract : We successfully developed an NIR light-triggered in vivo on–off tattoo system using hyaluronate modified upconversion nanoparticles for various biomedical applications. Abstract : An in vivo on–off tattoo system was developed using upconversion nanoparticles conjugated with hyaluronate (HA-UCNPs). Two-photon microscopy clearly visualized the transdermal delivery of HA-UCNPs into the deep skin tissue. Upon near-infrared light irradiation, invisible HA-UCNPs in the skin were visualized showing the feasibility as a new on–off tattoo system.